Future Acquisition by Iraqi EFL College Students (Journal of the College of Basic Education, 2022)
Tense is a grammatical category that locates a situation in time which indicates when the situation takes place. Tense is a part of grammar. Mastering tense is very important because if we do not use appropriate tense, it may cause misunderstanding especially in written language. Unfortunately students confuse with English tenses, even for the university students. They assume tenses as a big burden. Previous researches have proved that future tense is a complicated area of grammar since there are different ways of expressing this structure in English language. Hence the future tense is considered to be the most difficult structure for Iraqi learners of EFL, but none of the previous studies have tackled with the ability to recognize and produce this structure correctly. This study aims at:Studying the acquisition of futurity by Iraq EFL learners to decide whether they eventually succeed in acquiring it or not.Investigating the errors the learners made in recognizing and producing the future tense.